The Influence of Perceived Benefits, Perceived Ease of Use, and Service Features on Customer Satisfaction with the Use of the PLN Mobile Application at PT PLN (PERSERO) UP3 Palembang - Rosyada, Amrina; Alie, Juhaini (JEM17: Jurnal Ekonomi Manajemen, 2025)
The research objective is specifically to determine the influence of the variables Influence of Perceived Benefits, Perceived Convenience, and Service Features on Customer Satisfaction (Case Study on Using the PLN UP3 Palembang Mobile PLN Application)." partially or simultaneously. The research method uses questionnaire, interview and documentation techniques. The sample of this research was 80 employees on Customer Satisfaction (Case Study on the Use of the PLN Mobile PLN UP3 Palembang Application). Data processing used SPSS 23 analysis. Testing the data using the t test, that research had an effect on Perception of benefits with t table 0.909 < t count 1.992, Perception of convenience on customer satisfaction with t table -1.851 > t count 1.992, and Service features on customer satisfaction with t table 32,212 > t count 1,992 and Perception of Benefit, Perception of Convenience, and Service Features on Customer Satisfaction with F table 6,0304 < F count 1,992, the common thread of research is that the Influence of Perception of Benefit, Perception of Convenience, and Service Features on Customer Satisfaction requires improving service quality, conducting training for employees and always paying attention to product quality both in terms of service and quality so that customers remain loyal and continuously use the application. Keywords: Perceived Benefits, Perceived Convenience, Service Features, Customer Satisfaction.